Dynamic Modelling of Centrifugal Hydraulic Load of Pumping Station Electric Drive - Vladyslav Lysiak; Mykhailo Oliinyk; Olha Sivakova; Myroslav Sabat (Energy Engineering and Control Systems)
The paper analyzes modern trends in modelling the centrifugal hydraulic load of the pumping station electric drive. It was found that a very simplified approach to the representation of one of the inextricably linked subsystems (hydraulic or electromechanical) is mostly used, which significantly reduces the possibility of a complex analysis of the processes in its individual elements. Models based on this approach can be effectively applied to solve highly specialized tasks and do not always give a clear idea of ​​the state and modes of all the elements of the subsystems. This problem was partially solved while carrying out the simulation of the steady state modes of the pumping stations. The paper offers an advanced dynamic model of the centrifugal hydraulic load of the pumping station electric drive which enables studying the processes in the main elements of the centrifugal pump, taking into account its internal parameters and dependences of these parameters on the physical parameters of the fluid.